2018
DOI: 10.1186/s13024-018-0235-y
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson disease-associated mutations in LRRK2 cause centrosomal defects via Rab8a phosphorylation

Abstract: BackgroundMutations in LRRK2 are a common genetic cause of Parkinson’s disease (PD). LRRK2 interacts with and phosphorylates a subset of Rab proteins including Rab8a, a protein which has been implicated in various centrosome-related events. However, the cellular consequences of such phosphorylation remain elusive.MethodsHuman neuroblastoma SH-SY5Y cells stably expressing wildtype or pathogenic LRRK2 were used to test for polarity defects in the context of centrosomal positioning. Centrosomal cohesion deficits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(119 citation statements)
references
References 64 publications
7
110
0
Order By: Relevance
“…The subsequent and systematic analyses demonstrated that Rab3a-d, Rab5a-c, Rab8a/b, Rab10, Rab12, Rab29 (also known as Rab7L1), Rab35 and Rab43 are phosphorylated by LRRK2 at least upon overexpression (Steger et al, 2017). Other groups have also reported that Rab8, Rab10 and Rab29 behave as excellent substrates of LRRK2 in cells (Fujimoto et al, 2018;Liu et al, 2018;Madero-Perez et al, 2018a). At endogenous levels, LRRK2-mediated phosphorylation likely occurs on Rab3a-d, Rab8a/b, Rab10, Rab12, Rab35 and Rab43 (Steger et al, 2017).…”
Section: The Impact Of Rab Phosphorylation By Lrrk2mentioning
confidence: 93%
“…The subsequent and systematic analyses demonstrated that Rab3a-d, Rab5a-c, Rab8a/b, Rab10, Rab12, Rab29 (also known as Rab7L1), Rab35 and Rab43 are phosphorylated by LRRK2 at least upon overexpression (Steger et al, 2017). Other groups have also reported that Rab8, Rab10 and Rab29 behave as excellent substrates of LRRK2 in cells (Fujimoto et al, 2018;Liu et al, 2018;Madero-Perez et al, 2018a). At endogenous levels, LRRK2-mediated phosphorylation likely occurs on Rab3a-d, Rab8a/b, Rab10, Rab12, Rab35 and Rab43 (Steger et al, 2017).…”
Section: The Impact Of Rab Phosphorylation By Lrrk2mentioning
confidence: 93%
“…Similarly, Rab8A has also been shown to play a role in membrane trafficking and clearance as well as protein transport (Chung et al, 2017). Further evidence for the role of Rab8A in development and pathogenesis comes as studies have shown that LRRK2 phosphorylation of Rab8A can cause centrosomal defects and thus cause widespread effects on neurite growth and migration (Madero-Pérez et al, 2018a).…”
Section: Rab Proteinsmentioning
confidence: 99%
“…vesicle transport and membrane recycling to the cell surface(Banton et al, 2014), autophagy (with the ALS-related gene, C9orf72, implicated as a Rab8 GEF) (Corbier and Sellier, 2017), and has previously been linked to LRRK2 in, variously, endolysosomal trafficking(Rivero-Ríos et al, 2019), centrosome function(Madero-Pérez et al, 2018) and…”
mentioning
confidence: 99%